Education Of Safe Treatment Of Degenerative Diseases In The Elderly At The Miftahul Jannah Elderly Boarding - Ainun Muthoharoh; Dwi Bagus Pambudi; Slamet Slamet; Nabilatul Khusna; Ade Yunita Safira; Mahdanya Puteri AB; Sri Kusmaniyah; Asfal Fuad; Widyastuti Handayani (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
egenerative diseases are often experienced by the elderly, such as gout, high blood pressure, arthritis, high cholesterol and diabetes. Therefore, elderly people need to know more about diseases and treatments that can be used to prevent or reduce their symptoms. Community service activities were carried out targeting elderly mothers at the Miftahul Jannah Islamic Boarding Pimpinan Daerah ‘Aisyiyah (PDA) Pekalongan Regency. A total of 63 participants took part in this activity. This activity aims to provide knowledge about disease information and safe treatment of degenerative diseases in the elderly. The implementation method used the lecture and discussion method. Knowledge assessment was taken through a closed questionnaire and participants' responses during the discussion session. The conclusion that can be drawn from this activity is that elderly people need knowledge about medicines for degenerative diseases, which are common diseases suffered by elderly people. Participants enthusiastically paid attention and asked questions during the activity.